EFFECT OF MELATONIN ON SERUM GLUCOSE AND BODY WEIGHTS IN STREPTOZOTOCIN INDUCED DIABETES IN ALBINO RATS - Hidayat, Mariyah; Mahar, Yasmeen; Wasim, Bushra (Journal of Ayub Medical College Abbottabad, 2015)
Background: It has been demonstrated in experimental animal models that oxidative stress causes persistent and chronic hyperglycaemia, causing reduction in antioxidant defence system, ultimately leading to accumulation of free radicals.This study was performed to observe the effect of melatonin on serum glucose and body weights in streptozotocin induced diabetes in albino rats. Methods: Forty healthy adult male albino rats were included in the study and divided equally into 4 groups for 6 weeks. Group-A was taken as control. Group-B received streptozotocin I/P in a dose of 37 mg/kg body weight. Group-C received 10 mg/100 ml melatonin in drinking water and Group-D received only melatonin. Results: Streptozotocin significantly increased serum glucose and decreased weight in group B animals, whereas in group C, melatonin significantly restored serum glucose but could not restore the body weights reduced by streptozotocin. There was a significant reduction in body weight in melatonin treated group D animals. Conclusion: Melatonin decreases oxidative stress and hyperglycemia, but cannot restore the body weight reduced by streptozotocin. In fact, it further reduces body weight both in diabetic and normal state. Keywords: Streptozotocin, Melatonin, Oxidative stress, Reactive Oxygen Species, Diabetes Mellitus, Hyperglycaemia, Albino rats